2017
DOI: 10.1515/agp-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Upper Homerian (Silurian) high-resolution correlation using cyclostratigraphy: an example from western Lithuania

Abstract: ABSTRACT:Radzevičius, S., Tumakovaitė, B. and Spiridonov, A. 2017. Upper Homerian (Silurian) high-resolution correlation using cyclostratigraphy: an example from western Lithuania. Acta Geologica Polonica, 67 (2), 307-322. Warszawa.The Gėluva regional stage stratigraphically corresponds to the late Wenlock. This time interval witnessed significant graptolite extinctions and turnovers of conodont faunas, as well as a large positive Mulde carbon isotopic excursion. Thus, the development of a detailed stratigraph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…5) (Radzevičius et al 2014b). Similar cyclicities were found in other mid-upper Homerian geological sections of West Lithuania (Radzevičius et al 2017). The Gėluva age corresponds to the mid-later Homerian, namely from 428.45 ± 0.35 Ma to 427.86 ± 0.32 Ma (total ~ 0.59 Ma) (Cramer et al 2015).…”
Section: Trend In δ 13 C Org Valuessupporting
confidence: 81%
“…5) (Radzevičius et al 2014b). Similar cyclicities were found in other mid-upper Homerian geological sections of West Lithuania (Radzevičius et al 2017). The Gėluva age corresponds to the mid-later Homerian, namely from 428.45 ± 0.35 Ma to 427.86 ± 0.32 Ma (total ~ 0.59 Ma) (Cramer et al 2015).…”
Section: Trend In δ 13 C Org Valuessupporting
confidence: 81%
“…Similarly, previous synoptic studies have shown a close association of acritarch and prasinophyte diversity with global and regional fluctuations in sea level on time scales of millions to tens of millions of years , Delabroye et al 2011, Venckutë-Aleksienë et al 2016. This suggests the importance of sea level dynamics in modulating evolutionary and ecological change in Paleozoic marine phytoplankton as- th order sea level cycles (from (Radzevičius et al 2017). The smoothed non-linear trends in A-C were determined using 5 th order orthogonal polynomial regression.…”
Section: Trends In the Range Of Sizesmentioning
confidence: 61%
“…The studied core yielded one of the richest arrays of data in the world on the paleoenvironmental changes during the Mulde Event, ranging from graptolite, conodont, brachiopod, polychaete and microphytoplankton biostratigraphy and paleoecology, to stable carbon isotope chemostratigraphy and natural gamma ray cyclostratigraphy (Brazauskas & Paškevičius 1981;Paškevičius 1997;Martma et al 2005;Ekleris & Radzevičius 2014;Radzevičius et al 2014bRadzevičius et al , 2017Venckutë-Aleksienë et al 2016). Additionally, this core contains a stratotype of the lower boundary of the Gëluva regional stage (Kojelë et al 2014), and therefore it is a reference section for the detailed regional stratigraphical correlation and the detection of paleoclimatological and paleobiological patterns.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations